High Anxiety: Migration, Identity and Media in Crisis in Late Modern Period - Özkan, Devrim (International Journal of Contemporary Economics and Administrative Sciences, 2017)
This study analyses the social and political developments which bring national states and societies face to face with “migration” and “identity” problems in the “late modern period”. The fact that modern times are seeing the government being centralised day by day, increases identity and migration-related social problems. With the increase in ethnical and cultural variety, modern states face many problems with regards to regulating and controlling society. The fact that media are no longer a functional apparatus for organising and manipulating society leads to weakness in management. In this context, the present addresses the social problems and crises which have appeared in the “late modern period” in relation to migration, identity and media; indeed, these issues are analysed within the scope of the “high anxiety” concept. Moreover, discussion also focuses on the social relationship of “anxiety”, and the fact that it should be handled as one of the main factors affecting policy. There is also an analysis of the political and social problems which have arisen because of the crises of modern times. Indeed, modern society’s structural nature has increased “anxiety” levels very rapidly. In conclusion, it is considered that the problems stemming from the “structural” nature of modernity can be overcome with structural changes.